2020
DOI: 10.1177/2045894020968023
|View full text |Cite
|
Sign up to set email alerts
|

‘Tired, afraid, breathless … .’ An international survey of the exercise experience for people living with pulmonary hypertension

Abstract: Objectives: To identify patterns of exercise behaviour, attitudes towards exercise, barriers and enablers of exercise for people living with Pulmonary Hypertension (PH). Accessibility of rehabilitation services from a patient perspective was also explored. Methods: a voluntary, international survey of people living with PH was conducted, with mixed quantitative and qualitative data collection, in an online and paper format. Results: Data from 187 participants in 19 countries were included in the analyses. 52% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 31 publications
5
28
2
1
Order By: Relevance
“…However, it was a less commonly reported barrier (30% of respondents) compared to tiredness/fatigue (77%) and dyspnoea (71%). 7 The other study in PH 6 reported the primary exercise barriers as motivational (i.e., lack of self-discipline, lack of energy and lack of enjoyment). Fear was not cited as a barrier to exercise participation in the latter study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it was a less commonly reported barrier (30% of respondents) compared to tiredness/fatigue (77%) and dyspnoea (71%). 7 The other study in PH 6 reported the primary exercise barriers as motivational (i.e., lack of self-discipline, lack of energy and lack of enjoyment). Fear was not cited as a barrier to exercise participation in the latter study.…”
Section: Discussionmentioning
confidence: 97%
“…The association between previous adverse events during exercise and exercise-related concerns or anxiety has been reported previously. 7 …”
Section: Discussionmentioning
confidence: 99%
“… 16 Home-based interventions also provide solutions to common barriers to participation in centre-based programmes such as access and transport issues, and are less expensive. 17 Further, patient populations including PH 18 express a preference for unsupervised, self-paced, low-to-moderate intensity PA, specifically walking. 19 20 Through the use of telehealth, distance-based programmes could potentially offer an alternative mode of delivery for exercise training to increase adherence, availability and affordability for PH patients.…”
Section: Introductionmentioning
confidence: 99%
“…visit your physiotherapist for a detailed exercise program”—How often have we said this to our patients with pulmonary hypertension (PH), without realizing what it is that they feel about it or trying to understand why they have difficulties to carry out their exercise regime? A new paper by Chia and colleagues 1 in the current issue of Pulmonary Circulation has done just that—to identify the behaviors toward exercising, the potential barriers and facilitators, and the accessibility of these services through an international, online survey.…”
mentioning
confidence: 99%
“…The online survey conducted by Chia and colleagues 1 reached 202 participants from 19 countries around the world. With respondents coming mainly from Australia and New Zealand (over 60%) and targeted at well-educated, computer-literate individuals, the survey may represent a somewhat rosier view.…”
mentioning
confidence: 99%